Mechanical properties of sutures and knots used in oral surgery – an in vitro study - Łukaszuk, Kamila; Wojnicz, Dorota; Mierzejewska, Żaneta; Mierzejewski, Mateusz; Fiedorowicz, Katarzyna; Tołoczko-Iwaniuk, Natalia; Łukaszuk, Emilia; Sidun, Jarosław; Borys, Jan (Journal of Stomatology, 2017)
Introduction. Among the materials used for wound closure, surgical sutures are the ones most commonly used for this purpose. They are characterized by different mechanical properties. The type of thread and knot has significant impact on the security and stable close-up of wound edges, which allows proper healing. Aim of the study. To evaluate and compare durability of four kinds of threads and three different knots following the exposure to Ringer’s solution. Material and methods. The following were examined: durability and extendibility of four sutures and three surgical suture configurations: A. 2-1 (one double loop led to the right and one single loop led to the left), B. 2-2 (two double loops, one led the right, the other to the left), C. 1-1-1 (three single loops, the first and the third routed to the right, the other one to the left). The breaking force was measured by means of “Zwick Z010” device. Results. Mersilk and Dafilon threads had the same durability before and after the exposure, but after seven days they were more extendible. Threads bound with a knot (one double loop to the right and one single loop to the left) had worse durability and were the least susceptible to stretching. Conclusion. Stitches in the environment of the oral cavity are exposed to the forces unleashed during speech, deglutition and mastication. Therefore, it is critical to choose the correct suture along with the correct knot.